Psychoanalysis and Interdisciplinarity With Non-analytic Psychotherapeutic Approaches Through the Lens of Dialectics - Peri Herzovich, Yael; Govrin, Aner (Frontiers in Psychology, 2021)
Psychoanalysis, in its purist mainstream sense, tends to be considered as an isolationist discipline that steers clear of interdisciplinary connections with other psychotherapies. Its drive for purity does not open up to influences that cast as alien and a threat to its core principles. We refer to Hegelian dialectics in an attempt to offer an alternative approach to interdisciplinarity in clinical psychoanalysis. Psychoanalysis entertains a complex dialectical relationship with the major theories it opposes. In this dynamic, psychoanalysis begins by negating the non-psychoanalytic theory as a part of self-negation (Hegel calls this phase self-alienation). But in its own process of growth, it negates this negation and reabsorbs the alienated self part. Reabsorbing the negated component, psychoanalysis does not revert to its original identity but becomes sublated into a different, more complex idea. In this epistemological process, psychoanalysis deals with its own practical and theoretical anomalies and lacunas. The paper illustrates this process using three central developments in the history of psychoanalysis: empathy in self psychology (connection with Rogers' humanist psychology), short-term dynamic psychotherapy (connection with short, intensive therapies), and mentalization-based psychotherapy (connection with cognitive-behavioral therapies). In all of these cases, psychoanalysis integrates components it previously opposed and changes these components to their own, specific characteristics. We address the epistemological shifts in the scientific status of psychoanalysis and show their connection to dialectics. Finally, we conclude that dialectical development is what allows psychoanalysis to remain relevant and up to date, to be open to interdisciplinary influences without its identity and tradition coming under threat.